Respostas
respondido por:
1
Resposta:
n=21
Explicação passo-a-passo:
an=a1+(n-1)r
-66=-6+(n-1)-3
-66=-6+(-3n)+3
-66+6-3=-3n
-63=-3n
21=n
respondido por:
0
Resposta:
Espero ter ajudado. Boa noite!
Explicação passo-a-passo:
Basta jrogar a fórmula e fazer a substituição.
a1 = -6 e a2= -9 , onde an = -66
r = -3 e n = ???
an = ai + (n-1).r
-66 = -6 + (n-1) .(-3)
-66 = -6 - 3n + 3
-66 = -3n - 3
-66 + 3 = -3n
- 63 = -3n
n = -63 : (-3)
n= 21
Perguntas similares
5 anos atrás
5 anos atrás
5 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás